Nikolai Sergeyevich Korotkov: 120 years of his arterial blood pressure measurement method - Jelenković, Ankica (Vojnosanitetski pregled, 2026)
Nikolai Sergeyevich Korotkov (1874–1920) was a Russian military doctor and surgeon who discovered the technique of non-invasive measurement of arterial blood pressure. Measuring arterial blood pressure is possible based on the tones recorded with a stethoscope, now known as Korotkov sounds, using a sphygmomanometer. The tones disappear when the air pressure in the cuff placed around the upper arm exceeds the systolic pressure. The appearance of the first of a total of five tones occurs after the gradual deflation of the cuff and indicates the systolic pressure. It is several millimeters of mercury higher than that obtained by palpation of the radial artery, as was determined until then. The disappearance of the last, fifth tone, with a further reduction of air pressure in the cuff, indicates the diastolic pressure. Until that moment, measuring diastolic pressure in such a painless and simple manner had not been possible. Exactly 120 years have passed since Korotkov, at only 31 years of age, first announced his discovery in 1905 in Petrograd. The method was recognized by the professional community in 1939. Since then, Korotkov’s sounds have been accepted worldwide for measuring arterial blood pressure. This method has remained unsurpassed to this day.